A polymer functional filler prepared from coal gasification fine slag and its preparation method and application

Through dry ball milling or wet milling and surface modification technology, the problems of complex and contamination of fine slag treatment process in the existing technology are solved, and high-performance polymer functional fillers are prepared, achieving the goal of process simplification and environmental protection.

CN116063740BActive Publication Date: 2025-02-14INNER MONGOLIA YIDONG GROUP JIUDING CHEMICAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310273676.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-20
Publication Date
2025-02-14
Estimated Expiration
2043-03-20

AI Technical Summary

Technical Problem

The prior art has a complex process in the preparation of polymer functional fillers by gasifying fine slags, and requires the use of acid-soluble processes, which leads to pollution and waste slag generation, which violates the trend of green production.

Method used

The gasified fine slag is finely refined by dry ball milling or wet milling, and surface modification is performed by surface modification by surface modification to prepare polymer functional fillers. The process flow of this method is short, no acid-soluble process is required, and no waste residue is generated, and it is environmentally friendly and pollution-free.

Benefits of technology

It realizes effective fine refinement treatment and surface modification of coal gasified fine slag, improves the mechanical processing, aging and adsorption properties of polymer functional fillers on polymer matrix, and has an environmentally friendly and efficient process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116063740B_ABST
    Figure CN116063740B_ABST
Patent Text Reader

Abstract

The present invention provides a polymer functional filler prepared from coal gasification slag, a preparation method and application thereof, and belongs to the field of comprehensive utilization of solid waste. The present invention uses coal gasification slag as raw material, and performs micronization treatment on the coal gasification slag by dry ball milling or wet grinding, which can reduce the particle size of the coal gasification slag and improve its surface activity. At the same time, by using a surface modifier to perform surface modification treatment on the coal gasification slag, the polymer functional filler can have a good improvement effect on the mechanical processing performance, aging performance and adsorption performance of the polymer; the method provided by the present invention has a short process flow, and no acid dissolution or other processes are required in the preparation process, no waste slag is generated, and the preparation process is environmentally friendly and pollution-free.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of comprehensive utilization of solid waste, and in particular to a polymer functional filler prepared from coal gasification fine slag, and a preparation method and application thereof. Background Art

[0002] Coal gasification fine slag is the fine slag produced in the coal gasification production process. It is fine coal particles and fine ash that are not completely converted after high-temperature combustion and reaction in the gasifier. The fine coal particles are a bit similar to semi-coke. Usually, coal slime (gasification fine slag) contains 40-65% water, a certain amount of glass colloid produced by high temperature, is sticky, has no volatile matter, and has a residual carbon content of 21-30% (dry basis). The low calorific value of coal slime is 850-1200kcal / kg. Gasification slag includes coarse slag and fine slag. Coarse slag is the water-containing slag discharged from the slag lock bucket at the bottom of the gasifier after the slurry coal particles undergo processes such as melting, quenching, and condensation under the high temperature and high pressure conditions of the gasifier. The residual carbon content fluctuates greatly with the type of coal, the type of gasifier, and the operating conditions of the gasifier, and is generally 10-30%. The particle size is concentrated between 16 mesh and 4 mesh, and the amount produced accounts for about 80% of the gasification slag discharge; fine slag is the water-containing slag carried out from the top of the gasifier by the crude coal gas flow and obtained through preliminary washing, purification, and precipitation. The fine slag has a higher carbon residue content, generally reaching more than 30%, and the particle size is less than 16 mesh, of which about one-third is less than 200 mesh, and the amount produced accounts for about 20% of the gasification slag discharge. Coal gasification slag, whether coarse or fine, contains abundant silicon dioxide, aluminum oxide and iron oxide, the sum of which can reach more than 70%, meeting ASTM's Class F fly ash standard and having certain volcanic ash activity. In addition, coal gasification slag also contains inorganic substances such as calcium oxide, magnesium oxide and titanium dioxide.

[0003] Since the ash of coal gasification slag is easy to adhere, but there is no ash melting polymerization between the ash and the residual carbon, the residual carbon exists in a flocculent amorphous form and does not form small spheres with the ash. A large amount of coal gasification slag is stored in dams, which infiltrates and pollutes groundwater, occupies a large amount of land, and forms a large source of danger and pollution. At the same time, the dry fine powder of coal gasification slag after air drying flies with the wind, seriously polluting the atmospheric environment. In addition, the combustion of coal gasification slag is very similar to the combustion of ultrafine powder containing carbon and low calorific value, and the combustion is difficult, because the carbon particles are semi-coke, burned once at high temperature, have no volatile matter, and have a relatively low relative calorific value, so they cannot be burned alone. When added to other boilers, the carbon particles are fine, the residence time in the furnace is too short, and the specific gravity is easy to flow with the flue gas, and almost all of them are carried away with the flue gas, which makes it very difficult to burn. Therefore, the treatment of coal gasification slag has become a big problem.

[0004] Using coal gasification slag to prepare functional fillers is currently a common way to solve the problem of coal gasification slag. However, the existing technology uses acid dissolution and other processes to treat the coal gasification slag during the preparation process. Not only is the process complicated and lengthy, which does not conform to the development trend of green production, but the separation process in the existing technology will produce waste slag and other processes, which can easily cause secondary pollution.

[0005] Therefore, providing a method for preparing polymer functional fillers from coal gasification fine slag with a short process flow and an environmentally friendly and pollution-free preparation process has become a technical problem to be solved urgently in the field. Summary of the invention

[0006] The purpose of the present invention is to provide a polymer functional filler prepared from coal gasification fine slag, and a preparation method and application thereof. The method provided by the present invention has a short preparation process, and does not require the use of acid dissolution and other processes during the preparation process, and does not produce waste slag. The preparation process is environmentally friendly and pollution-free.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing polymer functional filler from coal gasification fine slag, comprising the following steps:

[0009] (1) mixing coal gasification fine slag, a grinding aid and medium balls and then dry-milling the mixture to obtain coal gasification fine slag powder;

[0010] Alternatively, the coal gasification fine slag is mixed with water to obtain a coal gasification fine slag suspension, and then a grinding aid and a medium ball are added to perform wet grinding to obtain a coal gasification fine slag grinding liquid;

[0011] (2) mixing the coal gasification fine slag powder obtained in step (1) with a surface modifier to perform surface modification treatment to obtain a polymer functional filler;

[0012] Alternatively, the coal gasification fine slag grinding liquid obtained in step (1) is mixed with a surface modifier to perform surface modification treatment, and then solid-liquid separation and drying are performed in sequence to obtain a polymer functional filler;

[0013] The surface modifier includes one or more of a silane coupling agent, a fatty acid, a fatty acid salt and a rare earth ion compound.

[0014] Preferably, in step (1), the rotation speed of the dry ball milling is 300 to 750 r / min, and the time of the dry ball milling is 150 to 300 min.

[0015] Preferably, the bulk density of the coal gasification fine slag powder in step (1) is 0.30 to 0.32 g / cm 3 The volume average particle size of the coal gasification fine slag powder is 1 to 5 μm.

[0016] Preferably, the mass percentage of the coal gasification fine slag in the coal gasification fine slag suspension in step (1) is 5 to 50%.

[0017] Preferably, the rotation speed of the wet grinding in step (1) is 500 to 1500 r / min, and the wet grinding time is 30 to 240 min.

[0018] Preferably, the volume average particle size of the solid particles in the coal gasification fine slag grinding liquid in step (1) is 5 to 10 μm.

[0019] Preferably, the amount of the surface modifier used in step (2) is 0.1 to 1.0 wt.% of the mass of the coal gasification fine slag in step (1).

[0020] The present invention provides a polymer functional filler prepared by the method described in the above technical solution.

[0021] The present invention provides the use of the polymer functional filler described in the above technical solution in a polymer matrix.

[0022] Preferably, the amount of the polymer functional filler is 10 to 45 wt.% of the mass of the polymer matrix.

[0023] The present invention provides a method for preparing a polymer functional filler from coal gasification fine slag, comprising the following steps: (1) mixing coal gasification fine slag, a grinding aid and a medium ball and then performing dry ball milling to obtain coal gasification fine slag powder; or, mixing coal gasification fine slag and water to obtain a coal gasification fine slag suspension, and then adding a grinding aid and a medium ball to perform wet grinding to obtain a coal gasification fine slag grinding liquid; (2) mixing the coal gasification fine slag powder obtained in the step (1) with a surface modifier and performing surface modification treatment to obtain a polymer functional filler; or, mixing the coal gasification fine slag grinding liquid obtained in the step (1) with a surface modifier and performing surface modification treatment, and then sequentially performing solid-liquid separation and drying to obtain a polymer functional filler; the surface modifier comprises one or more of a silane coupling agent, a fatty acid, a fatty acid salt and a rare earth ion compound. The present invention uses coal gasification fine slag as raw material, and performs micronization treatment on the coal gasification fine slag by dry ball milling or wet grinding, which can reduce the particle size of the coal gasification fine slag and improve its surface activity. At the same time, by using a surface modifier to perform surface modification treatment on the coal gasification fine slag, the polymer functional filler can have a good improvement effect on the mechanical processing performance, aging performance and adsorption performance of the polymer. The method provided by the present invention has a short process flow, and no acid dissolution or other processes are required in the preparation process, no waste residue is generated, and the preparation process is environmentally friendly and pollution-free. The results of the embodiment show that the polymer functional filler prepared by the method provided by the present invention can improve the mechanical properties of the polymer composite material after being added to the polymer matrix, such as the tensile strength of styrene-butadiene rubber can reach a maximum of 11.26MPa, and the tear strength reaches 45.77KN / m. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is the volume average particle size of the coal gasification fine slag powder after dry ball milling in Example 1 of the present invention;

[0025] Figure 2 is the volume average particle size of the coal gasification fine slag powder after dry ball milling in Example 2 of the present invention;

[0026] Figure 3 is the volume average particle size of the coal gasification fine slag powder after dry ball milling in Example 3 of the present invention;

[0027] Figure 4 is the volume average particle size of the coal gasification fine slag powder after wet grinding in Example 4 of the present invention;

[0028] Figure 5 is the volume average particle size of the coal gasification fine slag powder after wet grinding in Example 5 of the present invention;

[0029] Figure 6 is the volume average particle size of the coal gasification fine slag powder after wet grinding in Example 6 of the present invention;

[0030] Figure 7 This is a scanning electron microscope image of the polymer functional filler prepared in Example 6 of the present invention;

[0031] Figure 8 This is a scanning electron microscope image of the polymer functional filler prepared in Example 6 of the present invention;

[0032] Fig. 9 This is a scanning electron microscope image of the polymer functional filler prepared in Example 6 of the present invention;

[0033] Fig.10 This is a scanning electron microscope image of the polymer functional filler prepared in Example 6 of the present invention. DETAILED DESCRIPTION

[0034] The present invention provides a method for preparing polymer functional filler from coal gasification fine slag, comprising the following steps:

[0035] (1) mixing coal gasification fine slag, a grinding aid and medium balls and then dry-milling the mixture to obtain coal gasification fine slag powder;

[0036] Alternatively, the coal gasification fine slag is mixed with water to obtain a coal gasification fine slag suspension, and then a grinding aid and a medium ball are added to perform wet grinding to obtain a coal gasification fine slag grinding liquid;

[0037] (2) mixing the coal gasification fine slag powder obtained in step (1) with a surface modifier to perform surface modification treatment to obtain a polymer functional filler;

[0038] Alternatively, the coal gasification fine slag grinding liquid obtained in step (1) is mixed with a surface modifier to perform surface modification treatment, and then solid-liquid separation and drying are performed in sequence to obtain a polymer functional filler;

[0039] The surface modifier includes one or more of a silane coupling agent, a fatty acid, a fatty acid salt and a rare earth ion compound.

[0040] The invention mixes coal gasification fine slag, a grinding aid and a medium ball and then performs dry ball milling to obtain coal gasification fine slag powder.

[0041] In the present invention, the coal gasification fine slag is preferably coal pulverized furnace gasification residue. The present invention has no particular limitation on the specific source of the coal gasification fine slag, and coal gasification fine slag well known to those skilled in the art can be used. In one embodiment of the present invention, the coal gasification fine slag is preferably from Ejin Horo Banner, Ordos City, Inner Mongolia Autonomous Region.

[0042] The present invention has no special limitation on the basic physical and chemical properties of the coal gasification slag. In one embodiment of the present invention, the basic physical and chemical properties of the coal gasification slag are preferably: the carbon component content is 30-35wt.%, the moisture content is 55-65wt.%, the volume average particle size is 70.7μm, the particle size distribution range is 10-300μm, and the components of the coal gasification slag are all amorphous. The present invention uses the coal gasification slag with the above physical and chemical properties as raw material, which is conducive to micronization.

[0043] In the present invention, the coal gasification fine slag, grinding aid and medium balls are preferably mixed in the following manner: the coal gasification fine slag and grinding aid are first mixed evenly, and then the medium balls are added.

[0044] In the present invention, the grinding aid preferably includes one or more of triethanolamine, ethylene glycol, glycerol, sodium acetate, sodium hexametaphosphate, sodium tripolyphosphate, sodium silicate and sodium sulfate, and more preferably triethanolamine, ethylene glycol, glycerol, sodium acetate, sodium hexametaphosphate, sodium tripolyphosphate, sodium silicate and sodium sulfate; when the grinding aid is triethanolamine, ethylene glycol, glycerol, sodium acetate, sodium hexametaphosphate, sodium tripolyphosphate, sodium silicate and sodium sulfate, the present invention has no special restrictions on the proportion of each component, which can be determined according to the technical common sense of those skilled in the art. In the present invention, the amount of the grinding aid is preferably 0.5-1.5wt.% of the mass of the coal gasification fine slag, and more preferably 1.0wt.%. The present invention helps to improve the ball milling efficiency by adding the grinding aid.

[0045] In the present invention, the material of the dielectric ball is preferably one of polytetrafluoroethylene, alumina ceramics, zirconia ceramics and zirconium silicate, and more preferably one of polytetrafluoroethylene, alumina ceramics and zirconia ceramics; the amount of the dielectric ball is preferably 1 to 6 times the mass of the coal gasification fine slag, more preferably 2 to 5 times, and further preferably 3 to 4 times. The present invention can further improve the efficiency of ball milling by using the above-mentioned dielectric balls and controlling their amount.

[0046] In the present invention, the dry ball milling is preferably carried out in a ball mill, more preferably in a planetary ball mill. The present invention has no particular limitation on the specific model of the ball mill, and commercially available products known to those skilled in the art can be used.

[0047] In the present invention, the rotation speed of the dry ball mill is preferably 300-750 r / min, more preferably 350-700 r / min, and further preferably 400-650 r / min; the time of the dry ball mill is preferably 150-300 min, and more preferably 200-250 min. The present invention can make the particle size of the coal gasification fine slag powder meet the requirements by controlling the parameters of the dry ball mill.

[0048] After the dry ball milling is completed, the present invention preferably separates and dries the dry ball milling product in sequence to obtain coal gasification fine slag powder. The present invention has no particular limitation on the specific method of separation and drying, as long as the coal gasification fine slag powder can be separated from the medium balls and dried.

[0049] In the present invention, the bulk density of the coal gasification fine slag powder is preferably 0.30 to 0.32 g / cm 3 , more preferably 0.31 to 0.318 g / cm 3 , more preferably 0.317 to 0.318 g / cm 3 The volume average particle size of the coal gasification fine slag powder is preferably 1 to 5 μm, more preferably 2 to 4 μm. The present invention is beneficial to improving the improvement effect of the functional filler on the performance of the polymer matrix by controlling the parameters of the coal gasification fine slag powder.

[0050] The invention mixes coal gasification fine slag and water to obtain coal gasification fine slag suspension, then adds grinding aid and medium balls to perform wet grinding to obtain coal gasification fine slag grinding liquid.

[0051] In the present invention, the parameters of the coal gasification fine slag are preferably the same as the parameters of the coal gasification fine slag used in dry ball milling, which will not be described in detail herein.

[0052] In the present invention, the mass percentage of the coal gasification fine slag in the coal gasification fine slag suspension is preferably 5-50%, more preferably 10-45%, and further preferably 15-40%. The present invention is beneficial to improving the grinding efficiency of wet grinding by controlling the amount of coal gasification fine slag.

[0053] In the present invention, the grinding aid preferably includes one or more of triethanolamine, ethylene glycol, glycerol, sodium acetate, sodium hexametaphosphate, sodium tripolyphosphate, sodium silicate and sodium sulfate, and more preferably triethanolamine, ethylene glycol, glycerol, sodium acetate, sodium hexametaphosphate, sodium tripolyphosphate, sodium silicate and sodium sulfate; when the grinding aid is triethanolamine, ethylene glycol, glycerol, sodium acetate, sodium hexametaphosphate, sodium tripolyphosphate, sodium silicate and sodium sulfate, the present invention has no special restrictions on the proportion of each component, which can be determined according to the technical common sense of those skilled in the art. In the present invention, the amount of the grinding aid is preferably 0.5-1.5wt.% of the mass of the coal gasification fine slag, and more preferably 1.0wt.%. The present invention helps to improve the ball milling efficiency by adding the grinding aid.

[0054] In the present invention, the material of the medium ball is preferably zirconia ceramic or zirconium silicate ceramic; the amount of the medium ball is preferably 1 to 6 times the mass of the coal gasification fine slag, more preferably 2 to 5 times, and further preferably 3 to 4 times. The present invention can further improve the efficiency of wet grinding by using the above medium ball as the medium ball and controlling its amount.

[0055] In the present invention, the wet grinding is preferably carried out in a grinding mill. The present invention has no particular limitation on the specific model of the grinding mill, and commercial products well known to those skilled in the art can be used.

[0056] In the present invention, the rotation speed of the wet grinding is preferably 500-1500r / min, more preferably 800-1300r / min, and further preferably 900-1200r / min; the time of the wet grinding is preferably 30-240min, more preferably 60-210min, and further preferably 90-180min. The present invention can reduce the particle size of the coal gasification fine slag by performing a grinding and refining treatment by wet grinding, and can further improve the efficiency of the wet grinding by controlling the parameters of the wet grinding, so as to ensure that the physical and chemical parameters of the coal gasification fine slag powder meet the requirements.

[0057] In the present invention, the volume average particle size of the solid particles in the coal gasification fine slag grinding liquid is preferably 5 to 10 μm, more preferably 6 to 9 μm, and further preferably 7 to 8 μm. The present invention is beneficial to improving the improvement effect of the functional filler on the performance of the polymer matrix by controlling the parameters of the solid particles in the coal gasification fine slag grinding liquid.

[0058] After obtaining the coal gasification fine slag powder, the present invention mixes the coal gasification fine slag powder with a surface modifier to perform surface modification treatment to obtain a polymer functional filler.

[0059] In the present invention, the surface modifier includes one or more of a silane coupling agent, a fatty acid, a fatty acid salt and a rare earth ion compound, and more preferably one of a silane coupling agent, a fatty acid, a fatty acid salt and a rare earth ion compound. In the present invention, the silane coupling agent is preferably one or more of bis-(γ-triethoxysilylpropyl) tetrasulfide, bis(triethoxysilylpropyl) disulfide, γ-mercaptopropyltrimethoxysilane and γ-aminopropyltriethoxysilane; the fatty acid is preferably stearic acid; the fatty acid is preferably sodium stearate; the rare earth ion compound is preferably cerium oxide or lanthanum oxide. The present invention does not specifically limit the specific source of the surface modifier, and commercial products well known to those skilled in the art can be used. The present invention uses the above-mentioned surface modifier to perform surface modification treatment on coal gasification fine slag powder, which can enhance the interfacial bonding between coal gasification fine slag and polymer matrix and inhibit the agglomeration of coal gasification fine slag in the polymer matrix.

[0060] In the present invention, the amount of the surface modifier is preferably 0.1-1.0 wt.%, more preferably 0.2-0.8 wt.%, and further preferably 0.4-0.6 wt.% of the mass of the coal gasification fine slag. The modification effect can be further improved by controlling the amount of the surface modifier.

[0061] In the present invention, the temperature of the surface modification treatment is preferably 40 to 70°C, more preferably 50 to 60°C; the time of the surface modification treatment is preferably 20 to 60 minutes, more preferably 30 to 40 minutes. The present invention can further improve the modification effect by controlling the temperature and time of the surface modification treatment.

[0062] After the coal gasification fine slag is obtained by suspension grinding, the present invention mixes the coal gasification fine slag grinding liquid and a surface modifier to perform surface modification treatment, and then sequentially performs solid-liquid separation and drying to obtain a polymer functional filler.

[0063] In the present invention, the type and amount of the surface modifier are preferably the same as those described above, and will not be described in detail herein.

[0064] In the present invention, the time of the surface modification treatment is preferably 90 to 120 minutes, more preferably 100 to 110 minutes; the temperature of the surface modification treatment is preferably room temperature. In the present invention, the surface modification treatment is preferably carried out under stirring conditions. The present invention has no particular limitation on the stirring rate, as long as the surface modifier can be fully mixed with each component. The present invention can further improve the modification effect by controlling the temperature of the surface modification treatment.

[0065] In the present invention, the solid-liquid separation method is preferably a filter press or a suction filtration method; the drying method is preferably flash drying. The present invention does not specifically limit the specific parameters of the solid-liquid separation and drying, which can be determined according to the technical common sense of those skilled in the art. The present invention can separate the coal gasification fine slag powder and water by solid-liquid separation, and can remove the residual moisture in the coal gasification fine slag powder by drying, which is convenient for subsequent surface modification treatment.

[0066] The present invention uses coal gasification fine slag as raw material, and performs micronization treatment on the coal gasification fine slag by dry ball milling or wet grinding, thereby reducing the particle size of the coal gasification fine slag and improving its surface activity. At the same time, by performing surface modification treatment on the coal gasification fine slag by using a surface modifier, the polymer functional filler can have a good improvement effect on the mechanical processing performance, aging performance and adsorption performance of the polymer. The method provided by the present invention has a short process flow, and does not require the use of acid dissolution and other processes during the preparation process, does not generate waste slag, and the preparation process is environmentally friendly and pollution-free.

[0067] The present invention provides a polymer functional filler prepared by the method described in the above technical solution. The volume average particle size of the polymer functional filler provided by the present invention is preferably 1 to 10 μm.

[0068] The present invention provides a polymer functional filler prepared by the method described in the above technical solution or the use of the polymer functional filler described in the above technical solution in a polymer matrix.

[0069] In the present invention, the polymer matrix preferably includes rubber, styrene-butadiene rubber and polyethylene resin. In the present invention, the amount of the polymer functional filler is preferably 10-45wt.% of the mass of the polymer matrix. By controlling the amount of the polymer functional filler within the above range, the improvement effect on the mechanical processing performance, aging performance and adsorption performance of the polymer matrix can be further improved.

[0070] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0071] Example 1

[0072] A method for preparing polymer functional filler from coal gasification fine slag, comprising the following steps:

[0073] (1) First, 500 g of coal gasification slag and 7.5 g of grinding aid are uniformly mixed, then 2000 g of medium balls are added to the mixture and ball milled in a planetary ball mill, and then separated and dried in sequence to obtain coal gasification slag powder; the grinding aid is triethanolamine and ethylene glycol, and the mass ratio of triethanolamine to ethylene glycol is 1:1; the amount of the grinding aid is 1.5 wt.% of the mass of the coal gasification slag; the material of the medium ball is zirconia ceramic, and the amount of the medium ball is 4 times the mass of the coal gasification slag; the rotation speed of the ball mill is 300 r / min, and the ball milling time is 180 min;

[0074] (2) mixing the coal gasification fine slag powder obtained in step (1) with 3 g of a surface modifier for surface modification to obtain a polymer functional filler; the surface modifier is a silane coupling agent γ-aminopropyltriethoxysilane, and the amount of the surface modifier is 0.6 wt.% of the mass of the coal gasification fine slag; the surface modification treatment temperature is 60° C., and the surface modification treatment time is 30 min;

[0075] The coal gasification slag comes from Ejin Horo Banner, Ordos City, Inner Mongolia Autonomous Region; the basic physical and chemical properties of the coal gasification slag are: the carbon component content is 30-35wt.%, the moisture content is 55-65wt.%, the volume average particle size is 70.7μm, the particle size distribution range is 10-300μm, and the components of the coal gasification slag are all amorphous.

[0076] The parameters of the coal gasification fine slag powder prepared in step (1) of Example 1 were tested, and the results were as follows: Figure 1 As shown. Figure 1 It can be seen that the bulk density of the coal gasification fine slag powder is 0.318 g / cm 3 The volume average particle size of the coal gasification fine slag powder is 4.37 μm.

[0077] Example 2

[0078] A method for preparing polymer functional filler from coal gasification fine slag, comprising the following steps:

[0079] (1) First, 500 g of coal gasification slag and 5 g of grinding aid are uniformly mixed, and then 2000 g of medium balls are added to the mixture and then ball-milled in a planetary ball mill, and then separated and dried in sequence to obtain coal gasification slag powder; the grinding aid is triethanolamine, glycerol and sodium hexametaphosphate, and the mass ratio of triethanolamine, glycerol and sodium hexametaphosphate is 1:1:1; the amount of the grinding aid is 1wt.% of the mass of the coal gasification slag; the material of the medium ball is zirconia ceramic, and the amount of the medium ball is 4 times the mass of the coal gasification slag; the rotation speed of the ball mill is 600 r / min, and the ball milling time is 120 min;

[0080] (2) mixing the coal gasification fine slag powder obtained in step (1) with 4 g of a surface modifier for surface modification treatment to obtain a polymer functional filler; the surface modifier is a silane coupling agent bis-(γ-triethoxysilylpropyl) tetrasulfide and sodium stearate, the mass ratio of bis-(γ-triethoxysilylpropyl) tetrasulfide to sodium stearate is 1:1, and the amount of the surface modifier is 0.8 wt.% of the mass of the coal gasification fine slag; the surface modification treatment temperature is 60° C., and the surface modification treatment time is 30 min;

[0081] The coal gasification slag comes from Ejin Horo Banner, Ordos City, Inner Mongolia Autonomous Region; the basic physical and chemical properties of the coal gasification slag are: the carbon component content is 30-35wt.%, the moisture content is 55-65wt.%, the volume average particle size is 70.7μm, the particle size distribution range is 10-300μm, and the components of the coal gasification slag are all amorphous.

[0082] The parameters of the coal gasification fine slag powder prepared in step (1) of Example 2 were tested, and the results were as follows: Figure 2 As shown. Figure 2 It can be seen that the bulk density of the coal gasification fine slag powder is 0.317 g / cm 3 The volume average particle size of the coal gasification fine slag powder is 3.27 μm.

[0083] Example 3

[0084] A method for preparing polymer functional filler from coal gasification fine slag, comprising the following steps:

[0085] (1) First, 500 g of coal gasification slag and 7.5 g of grinding aid are uniformly mixed, then 2000 g of medium balls are added to the mixture and then ball-milled in a planetary ball mill, and then separated and dried in sequence to obtain coal gasification slag powder; the grinding aid is triethanolamine, ethylene glycol and sodium polyacrylate, and the mass ratio of triethanolamine, ethylene glycol and sodium polyacrylate is 1:1:1; the amount of the grinding aid is 1.5 wt.% of the mass of the coal gasification slag; the material of the medium ball is zirconia ceramic, and the amount of the medium ball is 6 times the mass of the coal gasification slag; the rotation speed of the ball mill is 600 r / min, and the ball milling time is 240 min;

[0086] (2) mixing the coal gasification fine slag powder obtained in step (1) with 5 g of a surface modifier for surface modification treatment to obtain a polymer functional filler; the surface modifier is a silane coupling agent bis(triethoxysilylpropyl) disulfide and stearic acid, the mass ratio of bis(triethoxysilylpropyl) disulfide to stearic acid is 1:1, and the amount of the surface modifier is 1.0 wt.% of the mass of the coal gasification fine slag; the surface modification treatment temperature is 60° C., and the surface modification treatment time is 30 min;

[0087] The coal gasification slag comes from Ejin Horo Banner, Ordos City, Inner Mongolia Autonomous Region; the basic physical and chemical properties of the coal gasification slag are: the carbon component content is 30-35wt.%, the moisture content is 55-65wt.%, the volume average particle size is 70.7μm, the particle size distribution range is 10-300μm, and the components of the coal gasification slag are all amorphous.

[0088] The parameters of the coal gasification fine slag powder prepared in step (1) of Example 3 were tested, and the results were as follows: Figure 3 As shown. Figure 3 It can be seen that the bulk density of the coal gasification fine slag powder is 0.313 g / cm 3 The volume average particle size of the coal gasification fine slag powder is 1.77 μm.

[0089] Example 4

[0090] A method for preparing polymer functional filler from coal gasification fine slag, comprising the following steps:

[0091] (1) 500 g of coal gasification slag and water are mixed to obtain a coal gasification slag suspension, and then 5 g of a grinding aid and 3000 g of a medium ball are added to perform wet grinding in a mill to obtain a coal gasification slag grinding liquid; the mass percentage of the coal gasification slag in the coal gasification slag suspension is 10%; the grinding aid is triethanolamine and sodium hexametaphosphate, and the mass ratio of triethanolamine to sodium hexametaphosphate is 1:1; the amount of the grinding aid is 1.0 wt.% of the mass of the coal gasification slag; the material of the medium ball is zirconia ceramic, and the amount of the medium ball is 6 times the mass of the coal gasification slag; the rotation speed of the wet grinding is 500 r / min, and the wet grinding time is 120 min;

[0092] (2) mixing the coal gasification fine slag grinding liquid obtained in step (1) with 2.5 g of a surface modifier, performing surface modification treatment under stirring conditions, then performing solid-liquid separation by filter pressing, and finally flash drying to obtain a polymer functional filler; the surface modifier is a silane coupling agent bis-(γ-triethoxysilylpropyl) tetrasulfide, and the amount of the surface modifier is 0.5 wt.% of the mass of the coal gasification fine slag; and the surface modification treatment time is 90 min;

[0093] The coal gasification slag comes from Ejin Horo Banner, Ordos City, Inner Mongolia Autonomous Region; the basic physical and chemical properties of the coal gasification slag are: the carbon component content is 30-35wt.%, the moisture content is 55-65wt.%, the volume average particle size is 70.7μm, the particle size distribution range is 10-300μm, and the components of the coal gasification slag are all amorphous.

[0094] The coal gasification fine slag grinding liquid in step (1) was wet tested by a laser particle size analyzer, and the results are as follows: Figure 4 As shown. Figure 4 It can be seen that the volume average particle size of the solid particles in the coal gasification fine slag grinding liquid is 6.39 μm.

[0095] Example 5

[0096] A method for preparing polymer functional filler from coal gasification fine slag, comprising the following steps:

[0097] (1) 500 g of coal gasification slag and water are mixed to obtain a coal gasification slag suspension, and then 5 g of a grinding aid and 1500 g of a medium ball are added to perform wet grinding in a mill to obtain a coal gasification slag grinding liquid; the mass percentage of coal gasification slag in the coal gasification slag suspension is 40%; the grinding aid is triethanolamine, ethylene glycol and sodium polyacrylate, and the mass ratio of triethanolamine, ethylene glycol and sodium polyacrylate is 1:1:1; the amount of the grinding aid is 1.0 wt.% of the mass of the coal gasification slag; the material of the medium ball is zirconia ceramic, and the amount of the medium ball is 3 times the mass of the coal gasification slag; the rotation speed of the wet grinding is 500 r / min, and the wet grinding time is 180 min;

[0098] (2) mixing the coal gasification fine slag grinding liquid obtained in step (1) with 5 g of a surface modifier, performing surface modification treatment under stirring conditions, then performing solid-liquid separation by filter pressing, and finally flash drying to obtain a polymer functional filler; the surface modifier is a silane coupling agent bis(triethoxysilylpropyl) disulfide, and the amount of the surface modifier is 1.0 wt.% of the mass of the coal gasification fine slag; and the surface modification treatment time is 120 min;

[0099] The coal gasification slag comes from Ejin Horo Banner, Ordos City, Inner Mongolia Autonomous Region; the basic physical and chemical properties of the coal gasification slag are: the carbon component content is 30-35wt.%, the moisture content is 55-65wt.%, the volume average particle size is 70.7μm, the particle size distribution range is 10-300μm, and the components of the coal gasification slag are all amorphous.

[0100] The coal gasification fine slag grinding liquid in step (1) was wet tested by a laser particle size analyzer, and the results are as follows: Figure 5 As shown. Figure 5 It can be seen that the volume average particle size of the solid particles in the coal gasification fine slag grinding liquid is 5.86 μm.

[0101] Example 6

[0102] A method for preparing polymer functional filler from coal gasification fine slag, comprising the following steps:

[0103] (1) 500 g of coal gasification slag and water are mixed to obtain a coal gasification slag suspension, and then 5 g of a grinding aid and 2000 g of a medium ball are added to perform wet grinding in a mill to obtain a coal gasification slag grinding liquid; the mass percentage of coal gasification slag in the coal gasification slag suspension is 30%; the grinding aid is triethanolamine, ethylene glycol and sodium polyacrylate, and the mass ratio of triethanolamine, ethylene glycol and sodium polyacrylate is 1:1:1; the amount of the grinding aid is 1.0 wt.% of the mass of the coal gasification slag; the material of the medium ball is zirconia ceramic, and the amount of the medium ball is 4 times the mass of the coal gasification slag; the rotation speed of the wet grinding is 600 r / min, and the wet grinding time is 180 min;

[0104] (2) mixing the coal gasification fine slag grinding liquid obtained in the step (1) with 2.5 g of a surface modifier, performing surface modification treatment under stirring conditions, then performing solid-liquid separation by filter pressing, and finally flash drying to obtain a polymer functional filler; the surface modifier is γ-mercaptopropyltrimethoxysilane and stearic acid, the mass ratio of γ-mercaptopropyltrimethoxysilane to stearic acid is 1:1, and the amount of the surface modifier is 0.5 wt.% of the mass of the coal gasification fine slag; and the surface modification treatment time is 120 min;

[0105] The coal gasification slag comes from Ejin Horo Banner, Ordos City, Inner Mongolia Autonomous Region; the basic physical and chemical properties of the coal gasification slag are: the carbon component content is 30-35wt.%, the moisture content is 55-65wt.%, the volume average particle size is 70.7μm, the particle size distribution range is 10-300μm, and the components of the coal gasification slag are all amorphous.

[0106] The coal gasification fine slag grinding liquid in step (1) was wet tested by a laser particle size analyzer, and the results are as follows: Figure 6 As shown. Figure 6 It can be seen that the volume average particle size of the solid particles in the coal gasification fine slag grinding liquid is 5.06 μm.

[0107] Figures 7-10 The following are scanning electron microscope images of the polymer functional filler prepared in Example 6 at different magnifications. Figures 7-10 It can be seen that the microstructure of the polymer functional filler includes amorphous carbon and microbeads ( Figure 7 This is the magnified morphology of the microbeads in the polymer functional filler with a magnification of Mag = 1.00KX. Figure 8 This is the magnified morphology of amorphous carbon in polymer functional filler with a magnification of Mag = 1.00KX. Fig. 9 This is the magnified morphology of the polymer functional filler with a magnification of Mag = 5.00KX. Fig.10This is an enlarged morphology of the polymer functional filler with a magnification of Mag=30.00KX), and the regional particle size of the particles has a good correspondence with that of Example 6.

[0108] Application Example 1

[0109] The polymer functional filler prepared in Example 1 is added to the polyethylene resin, wherein the amount of the polymer functional filler is 20 wt.% of the mass of the polyethylene resin, and then a filled polyethylene composite material is prepared by a twin-screw extruder;

[0110] The twin-screw extruder is divided into eight heating stages, and the temperatures are 155°C, 160°C, 165°C, 170°C, 170°C, 170°C, 170°C, and 175°C respectively.

[0111] Application Example 2

[0112] The polymer functional filler prepared in Example 2 is added to styrene-butadiene rubber, wherein the amount of the polymer functional filler is 30 wt.% of the mass of the styrene-butadiene rubber, and then a filled styrene-butadiene rubber composite material is prepared by a melt blending method;

[0113] The steps of the melt blending method are:

[0114] 1) mixing styrene-butadiene rubber on an open mill, thinly passing it three times, then adding weighed additives and polymer functional fillers and fully mixing them, and then making triangle bags to make the styrene-butadiene rubber, the additives and the polymer functional fillers more evenly mixed to obtain a rubber composite material; the additives are zinc oxide (ZnO), stearic acid (SA), an accelerator (NS) and sulfur (S), and the mass ratio of styrene-butadiene rubber, zinc oxide, stearic acid, accelerator and sulfur is 100:3:1:1:1.75;

[0115] 2) The rubber composite material obtained in step 1) is left to stand at room temperature for 24 hours to exhaust gas, and the test vulcanization time is recorded as t 90 Then the rubber composite material is vulcanized to obtain a vulcanized rubber compound; the process conditions of the vulcanization molding are 163°C×10MPa×t 90 ;

[0116] 3) vulcanizing the rubber obtained in step 2) for 24 hours, and cutting it into pieces using a special cutter to obtain a filled styrene-butadiene rubber composite material.

[0117] Application Example 3

[0118] The polymer functional filler prepared in Example 3 was added into the styrene-butadiene rubber. The amount of the polymer functional filler was 40 wt.% of the mass of the styrene-butadiene rubber. Other conditions were the same as those in Application Example 2.

[0119] Application Example 4

[0120] The polymer functional filler prepared in Example 4 is added to styrene-butadiene rubber, wherein the amount of the polymer functional filler is 35 wt.% of the mass of the styrene-butadiene rubber, and then a filled styrene-butadiene rubber composite material is prepared by a twin-screw extruder;

[0121] The twin-screw extruder is divided into eight heating stages, and the temperatures are 155°C, 160°C, 165°C, 170°C, 170°C, 170°C, 170°C, and 175°C respectively.

[0122] Application Example 5

[0123] The polymer functional filler prepared in Example 5 is added to polyethylene, wherein the amount of the polymer functional filler is 40 wt.% of the mass of the polyethylene, and then a filled polyethylene composite material is prepared by a twin-screw extruder;

[0124] The twin-screw extruder is divided into eight heating stages, and the temperatures are 155°C, 160°C, 165°C, 170°C, 170°C, 170°C, 170°C, and 175°C respectively.

[0125] Application Example 6

[0126] The polymer functional filler prepared in Example 6 is added to polyethylene, wherein the amount of the polymer functional filler is 40 wt.% of the mass of the polyethylene, and then a filled polyethylene composite material is prepared by a twin-screw extruder;

[0127] The twin-screw extruder is divided into eight heating stages, and the temperatures are 155°C, 160°C, 165°C, 170°C, 170°C, 170°C, 170°C, and 175°C respectively.

[0128] Comparative Example 1

[0129] Styrene butadiene rubber.

[0130] Comparative Example 2

[0131] Polyethylene resin.

[0132] The properties of the filled styrene-butadiene rubber composite materials obtained in Examples 2 to 3 were tested, and the results are shown in Table 1:

[0133] Table 1 Properties of the filled styrene-butadiene rubber composites obtained in Application Examples 2 to 3

[0134]

[0135] It can be seen from Table 1 that the polymer functional filler prepared in the present invention can improve the machining performance, aging performance and adsorption performance of the polymer matrix.

[0136] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing polymer functional filler from coal gasification fine slag, comprising: (1) mixing coal gasification fine slag, a grinding aid and medium balls and then dry-milling the mixture to obtain coal gasification fine slag powder; Alternatively, the coal gasification fine slag is mixed with water to obtain a coal gasification fine slag suspension, and then a grinding aid and a medium ball are added to perform wet grinding to obtain a coal gasification fine slag grinding liquid; (2) mixing the coal gasification fine slag powder obtained in step (1) with a surface modifier to perform surface modification treatment to obtain a polymer functional filler; Alternatively, the coal gasification fine slag grinding liquid obtained in step (1) is mixed with a surface modifier to perform surface modification treatment, and then solid-liquid separation and drying are performed in sequence to obtain a polymer functional filler; The surface modifier includes one or more of a silane coupling agent, a fatty acid, a fatty acid salt and a rare earth ion compound; The bulk density of the coal gasification fine slag powder in step (1) is 0.30-0.32 g / cm 3 The volume average particle size of the coal gasification fine slag powder is 1 to 5 μm.

2. The method according to claim 1, characterized in that In the step (1), the rotation speed of the dry ball milling is 300 to 750 r / min, and the time of the dry ball milling is 150 to 300 min.

3. The method according to claim 1, characterized in that In the step (1), the mass percentage of the coal gasification fine slag in the coal gasification fine slag suspension is 5 to 50%.

4. The method according to claim 1, characterized in that The rotation speed of the wet grinding in the step (1) is 500 to 1500 r / min, and the wet grinding time is 30 to 240 min.

5. The method according to claim 1, characterized in that The volume average particle size of the solid particles in the coal gasification fine slag grinding liquid in the step (1) is 5 to 10 μm.

6. The method according to claim 1, characterized in that The amount of the surface modifier used in step (2) is 0.1 to 1.0 wt.% of the mass of the coal gasification fine slag in step (1).

7. The polymer functional filler prepared by the method according to any one of claims 1 to 6.

8. Use of the polymer functional filler according to claim 7 in a polymer matrix.

9. The use according to claim 8, characterized in that: The amount of the polymer functional filler is 10-45 wt.% of the mass of the polymer matrix.

Citation Information

Patent Citations

  • Method for preparing rubber filler by taking coal gasification slag as raw material

    CN112430400A